2015
DOI: 10.3892/mmr.2015.3334
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin induces autophagic cell death in prostate cancer cells in vitro

Abstract: Abstract. Athough it is well known that apoptosis contributes to cancer cell death, the role of autophagy in cancer cell death has remained in dispute. Atorvastatin has been suggested to exhibit anti-cancer effects. The present study aimed to examine atorvastatin-induced autophagy-associated cell death and the autophagy-associated gene expression profile in the PC3 prostate carcinoma cell line. The atorvastatin-induced process of autophagy in PC3 cells was determined via evaluation of the cellular expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…Breast cancer cells showed Beclin-1 and LC3B immunoreactivity and widened perinuclear cisterna, induced by stress depending atorvastatin treatment. Increased vacuolization and engulfment of membrane residues and/or cytoplasm by autophagic vesicles may be attributed to autophagy, and these changes were more prominently observed in MCF-7 cells treated with 10 and 20 μM atorvastatin for 48 h. Our results confirm previous studies that showed autophagic effects of atorvastatin on different kinds of cancer cell lines ( 10 , 11 , 12 , 13 , 14 ). Atorvastatin induced autophagic alterations in MCF-7 cells even at the lowest doses used.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Breast cancer cells showed Beclin-1 and LC3B immunoreactivity and widened perinuclear cisterna, induced by stress depending atorvastatin treatment. Increased vacuolization and engulfment of membrane residues and/or cytoplasm by autophagic vesicles may be attributed to autophagy, and these changes were more prominently observed in MCF-7 cells treated with 10 and 20 μM atorvastatin for 48 h. Our results confirm previous studies that showed autophagic effects of atorvastatin on different kinds of cancer cell lines ( 10 , 11 , 12 , 13 , 14 ). Atorvastatin induced autophagic alterations in MCF-7 cells even at the lowest doses used.…”
Section: Discussionsupporting
confidence: 90%
“…Autophagy is a type of cell death process by which cells recycle their unessential organelles and components under stress conditions ( 9 ). It provides new insight into cell death pathways, especially in cancer where it is thought to have a dual role ( 10 , 11 , 12 , 13 ). Thus, autophagy may behave both as a tumor suppressor by preventing accumulation of damaged organelles and misfolded proteins or as a cell survival mechanism by promoting the development of tumors ( 12 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies have indicated that autophagy inhibition sensitizes tumor cells to a wide spectrum of cancer therapies, while others have shown that treatment-induced tumor cell death requires intact autophagic machinery (2732). For instance, atorvastatin is considered by some to cause autophagy to promote apoptosis in human prostate cancer cells (33), whilst others have a contrasting views, and consider that inhibition of autophagy potentiates atorvastatin-induced apoptotic cell death (34). Although there is known crosstalk between autophagy and apoptosis, since they share certain signaling pathways and proteins, the mechanism where this bridging occurs has not been fully defined (35).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological survey indicated that use of statin drugs is linked to reduction in the risk of advanced prostate cancer . Atorvastatin (3‐hydroxy‐3‐methylglutaryl‐CoA (HMG‐CoA) reductase inhibitor), widely used for the prevention and treatment of hypercholesterolemia, has been shown to inhibit the proliferation and induce apoptosis of prostate cancer cells in vitro . Moreover, inflammation has been linked with the development and progression of BPH , and the presence of intraprostatic inflammatory infiltrations in BPH tissues such as IL‐17, COX‐1, and COX‐2 has been reported .…”
Section: Introductionmentioning
confidence: 99%